2020
DOI: 10.21786/bbrc/13.7/14
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Triphala Incorporated Zinc Oxide Nanoparticles and Assessment of its Antimicrobial Activity Against Oral Pathogens : An In-Vitro Study

Abstract: Triphala, a traditional Ayurveda herbal formulation consisting of dried fruits of three medicinal plants, is known to have effective antimicrobial properties. Inorganic elements like zinc oxide have also been known to have antimicrobial properties against strains of gram positive and gram negative bacteria, both. Green synthesis of nanoparticles is being encouraged, because of its positive effects on the environment and its cost-effectiveness. Hence, the study was conducted to synthesize Triphala augmented Zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…4. Previous research works have reported on the various activities exhibited by the nanoparticles synthesized from natural sources such as antibacterial, antioxidant and cytotoxic activity [49][50][51]. In a study, silver nanoparticles were synthesized from aqueous leaf extract of Cestrum nocturnum and its antioxidant and antibacterial activities were tested against bacteria and the results confirmed that the silver nanoparticles have more antioxidant activity as compared to vitamin C [52].…”
Section: Antioxidant Activity Of Silver Nanoparticles Using F Benghal...mentioning
confidence: 86%
“…4. Previous research works have reported on the various activities exhibited by the nanoparticles synthesized from natural sources such as antibacterial, antioxidant and cytotoxic activity [49][50][51]. In a study, silver nanoparticles were synthesized from aqueous leaf extract of Cestrum nocturnum and its antioxidant and antibacterial activities were tested against bacteria and the results confirmed that the silver nanoparticles have more antioxidant activity as compared to vitamin C [52].…”
Section: Antioxidant Activity Of Silver Nanoparticles Using F Benghal...mentioning
confidence: 86%
“…Many previous reports have recommended the possible use of plant extracts in oral care for effective and efficient inhibition of microflora by natural antimicrobials (31,34)(10). Nevertheless, the potential benefits of chemotherapeutic formulations in mouth rinses provide thrust for research in verdict effective mouth rinses for oral care [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In biosensing applications, ZnO NPs exhibit high catalytic efficiency, strong adsorption capability, a high isoelectric point, biocompatibility, and rapid electron transfer kinetics. Additionally, they find utility in various domains such as optical, piezoelectric, magnetic, and gas sensing [5]. C. serrulata, a marine submerged angiosperm, is commonly found in tidal and submerged coastal areas.…”
Section: Introductionmentioning
confidence: 99%